Psycholinguistic Approach: In the Case of Foreign Language Teaching - Farogat Bakhtiyorqizi Begibaeva (PT. Antis International Publisher, 2024)
The article provides information about the fact that learning a foreign language with a set of methods of various disciplines is an urgent task of scientific knowledge. The study of the ability to learn foreign languages is carried out using psycholinguistic methods based on contractual forms of communication, taking into account the individual characteristics of speakers, as well as the level of their language culture, semantics and elements of speech.